Role of slow temporal modulations in speech identification for cochlear implant users. (January 2014) - Gnansia, Dan; Lazard, Diane S.; Léger, Agnès C.; Fugain, Claude; Lancelin, Denis; Meyer, Bernard; Lorenzi, Christian
Abstract Objective: This study aimed to assess whether the capacity of cochlear implant (CI) users to identify speech is determined by their capacity to perceive slow (< 20 Hz) temporal modulations. Design: This was achieved by studying the correlation between (1) phoneme identification in quiet and in a steady-state or fluctuating (8 Hz) noises, and (2) amplitude-modulation detection thresholds (MDTs) at 8 Hz (i.e. slow temporal modulations). Study sample: Twenty-one CI users, unilaterally implanted with the same device, were tested in free field with their everyday clinical processor. Results: Extensive variability across subjects was observed for both phoneme identification and MDTs. Vowel and consonant identification scores in quiet were significantly correlated with MDTs at 8 Hz (r = − 0.47 for consonants, r = − 0.44 for vowels; p < 0.05). When the masker was a steady-state noise, only consonant identification scores tended to correlate with MDTs at 8 Hz (r = − 0.4; p = 0.07). When the masker was a fluctuating noise, consonant and vowel identification scores were not significantly correlated with MDTs at 8 Hz. Conclusions: Sensitivity to slow amplitude modulations is correlated with vowel and consonant perception in CI users. However, reduced sensitivity to slow modulations does not entirely explain the limited capacity of CI recipients to understand speech in noise.